Comparison of dexamethasone and clonidine as an adjunct to bupivacaine in transversus abdominis plane block in patients undergoing lower segment caesarean section - Falia, Mitesh D.; Kulkarni, Prasad (International Journal of Research in Medical Sciences, 2016)
Background: A lower segment caesarean section (LSCS) commonly induces moderate to severe postoperative pain for 48 hours. Aim of the study was to compare 0.25% bupivacaine with dexamethasone and 0.25% bupivacaine with clonidine for transversus abdominis plane (TAP) block as post-operative analgesia in patients undergoing lower segment caesarean section (LSCS). Methods: A randomized prospective controlled clinical study was conducted in 104 patients undergoing LSCS. Participants were divided into two groups in which group TAP-D (n=54) received 0.25% Bupivacaine with Dexamethasone 4mg and those in group TAP-C (n=50) received 0.25% Bupivacaine with Clonidine 75mcg as TAP block at the end of surgery. The postoperative pain was evaluated by visual analog scale (VAS) for pain scoring at every 2 hours for 12 hours postoperatively. Subjective assessment of duration of analgesia was done. Results: The average duration of analgesia with TAP bock for the overall study population was 316.15 minutes. The average VAS score in patients who received TAP with dexamethasone was 1.50 which is significantly lower than those who received clonidine (1.95) (P value-0.0001). Further the duration of analgesia was 151 minutes longer in the first group who received dexamethasone TAP. In majority of the patients (84%) who received clonidine TAP, the analgesia persisted for 2-4 hours. While in patients who received dexamethasone addition, the analgesia persisted for 6-8 hours in 37%. Conclusions: TAP block is a safe and effective way of relieving postoperative pain in LSCS patients. Addition of dexamethasone to bupivacaine significantly enhances its effect in terms of block quality and analgesia duration as compared to clonidine addition.